Pembuatan Sistem Informasi Untuk Kendaraan Listrik Otonom Berbasis Website - Aprillia Damayanti; Denden Mohamad Arifin; Ardian Infantono; Arief Suryadi Satyawan; Mohammed Ikrom Asysyakuur; Ema Ema; Raden Aditya Satria Nugraha (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
Current developments have made website technology a means of disseminating information that offers various conveniences and speeds in its presentation. Speed ​​and convenience are positive values ​​of the existence of the internet. The website is more easily accessible by people in various regions just by using the internet. One of them is in terms of marketing the product of a business, the website can be a means of promoting, marketing and conveying information effectively and efficiently to the public. One of the things that can be utilized from website technology is for information purposes of autonomous electric vehicles. This vehicle technology in the future can be integrated on the website for the purpose of information on its existence and condition. In fact, it is possible to create applications for the use of autonomous electric vehicles by making calls through the website, as is the case with applications that are currently popular, namely Gojek or Grab. In this study, a web application was developed for the purposes of a simple autonomous electric vehicle, which operates in the Nurtanio University Bandung campus environment. This website design consists of five pages. The first page contains a homepage where general information on research activities for the development of simple autonomous electric vehicles is found. The second page contains object detection which displays more detailed information about the object detection technology used in autonomous electric vehicles. Information on the existence of autonomous electric vehicles in the campus environment is then shown on the third page, namely Av Tracker. This website design is also equipped with a contributor page (page four) which contains researchers involved in autonomous electric vehicle research. At the end, the fifth page is for contact information for those who are interested in communicating further about matters related to this research. This website design uses a markup language consisting of HTML and CSS, besides that PHP and MySQL programming languages ​​are also used as databases.